2014
DOI: 10.1093/fampra/cmu048
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control and cardiovascular risk factors in type 2 diabetes mellitus patients according to diabetes duration

Abstract: The degree of glycaemic control and the risk factors in relation to the duration of T2DM followed different patterns. Diabetes duration was associated with a poorer glycaemic control but in general had a limited role in blood pressure control or lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
5
9
1
3
Order By: Relevance
“…The estimated worsening of diabetes control with an increasing number of complications, disease duration and intensification of treatment, same as a worse glycaemic control in the patients treated with insulin compared to oral therapy users in the T2DM group, agrees with the previously published data (10, 12, 19). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The estimated worsening of diabetes control with an increasing number of complications, disease duration and intensification of treatment, same as a worse glycaemic control in the patients treated with insulin compared to oral therapy users in the T2DM group, agrees with the previously published data (10, 12, 19). …”
Section: Discussionsupporting
confidence: 91%
“…Our data showed that 55.3% of patients achieved HbA1c < 7% which is worse than the average result in other European countries – 62.6%, reported in the Panorama study (22), but falls in between countries, where the percentage of T2DM patients reaching the target HbA1c ≤ 7 varies from 48.1 to 76.0% (10, 12, 19, 21, 23). …”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The maintenance of stable blood pressure throughout the 5-year study is particularly noteworthy in the elderly and patients with DM who are more likely to have hypertension (31, 32) Indeed, age-dependent changes would likely become evident during this period in DM patients. For example, blood pressure may be expected to increase by approximately 1 mmHg (33, 34) and, in patients with type 2 diabetes, HbA1c has been shown to deteriorate by 0.5% per year (35). However, long-term trends should be interpreted with caution given that there was no control group, the number of subjects was small and changes in antidiabetic, antihypertensive and lipid-lowering medications were not recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Длительность СД2 является одним из наиболее важ-ных показателей наличия осложнений СД, поскольку тесно связана со скоростью прогрессирования атеро-склероза [50], вновь акцентируя внимание на эффекте «метаболической памяти». И здесь важно понимать, что именно метформин обосновал целое направле-ние современной диабетологии: влияние сахаросни-жающей терапии не только путем контроля гликемии, но и за его пределами [6].…”
Section: диагностика контроль лечение Diagnosis Control Treatmentunclassified